Hubungan antara Kerusakan DNA dan Mekanisme Perbaikan Seluler: Tinjauan Literatur - Azizah Zahra Nur Fitria; Margaretha Alesandria Natasya Weka; Azlinatul Lulu Kharolaini; Desi Rahmasari; Pramai Sheila Eka Khoireina; Feni Atika Tsuroyya; Septi Puspita Kurniawati; Tyara Avrilyanti Ghea Indriansyah; Liss Dyah Dewi Arini (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2026)
DNA damage is a fundamental biological phenomenon that occurs due to endogenous and exogenous factors such as radiation, chemical exposure, and replication errors. If not properly repaired, DNA damage can lead to genomic instability, mutations, and the development of various diseases, including cancer. This literature review aims to examine the relationship between DNA damage and cellular repair mechanisms in maintaining genomic integrity. The method used in this study is a literature review of national scientific journals that discuss types of DNA damage, molecular markers of DNA damage, and cellular repair pathways. The findings indicate that cells possess complex and coordinated DNA repair systems, including base excision repair, nucleotide excision repair, mismatch repair, and double-strand break repair mechanisms, which play crucial roles in preserving cellular stability. The effectiveness of these repair mechanisms is influenced by the type and extent of DNA damage. Understanding the interaction between DNA damage and repair pathways provides important implications for the development of disease prevention strategies, diagnostic biomarkers, and therapeutic approaches in molecular biology and medical sciences.